2014
DOI: 10.1515/hsz-2014-0137
|View full text |Cite
|
Sign up to set email alerts
|

Netherton syndrome: defective kallikrein inhibition in the skin leads to skin inflammation and allergy

Abstract: Netherton syndrome (NS) is an orphan genetic skin disease with a profound skin barrier defect and severe allergic manifestations. NS is caused by loss of function mutations in SPINK5 encoding lympho-epithelial Kazal-type inhibitor (LEKTI), a secreted multi-domain serine protease inhibitor expressed in stratified epithelia. Studies in mouse models and in NS patients have established that unopposed kallikrein 5 activity triggers stratum corneum detachment and activates PAR-2 signaling, leading to the autonomous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 109 publications
(142 reference statements)
0
61
0
3
Order By: Relevance
“…Some patients also experience severe sepsis and cutaneous infections with viruses such as HPV, presumably because of the skin lesions. The phenotype, genotype, and mouse models have all recently been reviewed [185, 187-190]. In addition, filaggrin ( FLG ) deficiency can lead to impaired keratinization and defective skin barriers, which result in ichthyosis vulgaris and in some patients with elevated serum IgE [191-193].…”
Section: Other Syndromes In Which Ige Levels Are Highmentioning
confidence: 99%
“…Some patients also experience severe sepsis and cutaneous infections with viruses such as HPV, presumably because of the skin lesions. The phenotype, genotype, and mouse models have all recently been reviewed [185, 187-190]. In addition, filaggrin ( FLG ) deficiency can lead to impaired keratinization and defective skin barriers, which result in ichthyosis vulgaris and in some patients with elevated serum IgE [191-193].…”
Section: Other Syndromes In Which Ige Levels Are Highmentioning
confidence: 99%
“…LEKTI is expressed in both the epithelia and the thymus. Murine models have shown that LEKTI deficiency leads to unopposed kallikrein-related peptidase activity, ultimately causing impaired epidermal differentiation, defective cornification and poor skin barrier formation [136, 142, 143]. …”
Section: Dermatologic Syndromes With Immunodysregulation Associatedmentioning
confidence: 99%
“…At birth, an ichthyosiform erythroderma is usually observed . ILC consists on erythematous migratory polycyclic patches surrounded by serpiginous double‐edged scales, which is the typical cutaneous manifestation of this syndrome …”
Section: Discussionmentioning
confidence: 99%